2017
DOI: 10.1155/2017/2865912
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid Prevents Diabetic Nephropathy by Activating AMPK/SIRT1/PGC-1α Signaling in db/db Mice

Abstract: Diabetic nephropathy (DN) is a major cause of end-stage renal disease (ESRD). Glycyrrhizic acid (GA) is an effective inhibitor of reactive oxygen species (ROS) production. We investigated the role of GA in the progression of renal injury in DN. Albumin (Alb)/creatinine (crea) levels were significantly lower, and renal histopathology was attenuated in the diabetic db/db mice that were treated with GA (15 mg/kg via intraperitoneal injection) once per day for eight weeks. These changes were associated with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…Containing the key phytochemical GA, licorice is generally associated with detoxication in TCM [56], and exhibits antiviral effect [57][58][59]. Others have found that GA activates SIRT1 in diabetic db/db mice [60] and increases the expression of SIRT1 in renal tubular epithelial cell line [61]. Hence, it is speculated that GA may exert anti-CoV effects via regulating SIRT 1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Containing the key phytochemical GA, licorice is generally associated with detoxication in TCM [56], and exhibits antiviral effect [57][58][59]. Others have found that GA activates SIRT1 in diabetic db/db mice [60] and increases the expression of SIRT1 in renal tubular epithelial cell line [61]. Hence, it is speculated that GA may exert anti-CoV effects via regulating SIRT 1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that puerarin, an extract from a Chinese herbal medicine, attenuates diabetic kidney injury through activation of SIRT1 and suppression of NOX4 expression in podocytes in experimental diabetic mouse model ( 62 ). Other herbal medicines or compounds have also been reported to improve DKD through activation of SIRT1 ( 36 , 38 ). Metformin is reported to improve podocyte function by activating SIRT1 ( 66 ).…”
Section: Sirt1 Is a Potential Drug Target For Treatment Of Dkdmentioning
confidence: 99%
“…It mainly consists of triterpenes and flavonoids [4]. Glycyrrhizic acid and liquiritin are known as the main bioactive compounds in licorice in anti‐inflammation [5], preventing cancer [6,7], diabetic nephropathy [8], and hyperprolactinemia‐associated disorders [9]. The contents of glycyrrhizic acid and liquiritin varied from geographical origins [10,11].…”
Section: Introductionmentioning
confidence: 99%